Frequency of Intra-Dialytic Complications (Journal of Fatima Jinnah Medical University, 2018)
Objective: Haemodialysis is the most common therapeutic modality for the end stage renal disease. However it is associated with certain complications that need to be carefully monitored and rectified. In third world countries, like Pakistan, the frequency of these complications may be different from centre to centre from what has been already reported due to many factors like, variable standardization of machines, delayed referral of patients with end stage renal disease, inadequate dose of dialysis, socioeconomic restraints and poor compliance of the patients. This study was designed to find the frequency of intradialytic complications in haemodialysis unit, at Sheikh Zayed hospital, Lahore. Study Design: Single centred observational study. Setting: Haemodialysis unit, nephrology department, Sheikh Zayed hospital, Lahore. Patients and Methods: In this study total of 107 patients were enrolled using non-randomized convenient samplings, out of which 7 patients were lost to follow up. So study was conducted on 100 patients. All these patients having permanent vascular access (AV fistula) were dialyzed on machines with makes (models) that include, Fresenius, Toray and Nipro. All the dialysis sessions over a period of two months (2000 sessions) were monitored for the occurrence of the various complications. Results: Vomiting was most frequent complication observed in7% of dialysis sessions followed by fever and chills 4.6%, hypotension 4.2%, headache 1.2%, chest pain 1.2%, cramps 0.7%, backache 0.5% and itches 0.4%. Discussion: Due to availability of modern equipment, supervised dialysis sessions by trained doctors and paramedical staff, increase awareness among the patients regarding dose of dialysis, diet and drugs; there is significant difference in frequency of complications. However further steps should be taken to minimize the life threatening complications
Keywords: Haemodialysis, intradialytic complications